Impact of storm runoff on Salmonella and Escherichia coli prevalence in irrigation ponds of fresh produce farms in southern Georgia - Harris, C.S. (J Appl Microbiol, 2018)
AIMS: To examine Salmonella and Escherichia coli in storm runoff and irrigation ponds used by fresh produce growers, and compare Salmonella serovars with those found in cases of human salmonellosis. METHODS AND RESULTS: We collected water before and after rain events at two irrigation ponds on farms in southern Georgia, USA, and collected storm runoff/storm flow within the contributing watershed of each pond. Salmonella and E. coli concentrations were higher in ponds after rain events by an average of 0.46 (P < 0.01) and 0.61 (P < 0.05) log(10) most probable number (MPN) 100 ml(−1), respectively. Salmonella concentrations in storm runoff from fields and forests were not significantly higher than in ponds before rain events, but concentrations in storm flow from streams and ditches were higher by an average of 1.22 log(10) MPN 100 ml(−1) (P < 0.001). Eighteen Salmonella serovars were identified from 155 serotyped isolates, and eight serovars were shared between storm runoff/storm flow and ponds. Seven of the serovars, including five of the shared serovars, were present in cases of human illness in the study region in the same year. However, several serovars most commonly associated with human illness in the study region (e.g. Javiana, Enteritidis, and Montevideo) were not found in any water samples. CONCLUSIONS: Salmonella and E. coli concentrations in irrigation ponds were higher, on average, after rain events, but concentrations of Salmonella were low, and the ponds met FDA water quality standards based on E. coli. Some similarities and notable differences were found between Salmonella serovars in water samples and in cases of human illness. SIGNIFICANCE AND IMPACT OF STUDY: This study directly examined storm runoff/storm flow into irrigation ponds and quantified increases in Salmonella and E. coli following rain events, with potential implications for irrigation pond management as well as human health.